Multi-omics characterization of the microbial populations and chemical space composition of a water kefir fermentation - Arrieta-Echeverri, Maria Clara; Fernandez, Geysson Javier; Duarte-Riveros, Adriana; Correa-Álvarez, Javier; Bardales, Jorge Adalberto; Villanueva-Mejía, Diego Fernando; Sierra-Zapata, Laura (Frontiers in Molecular Biosciences, 2023)
In recent years, popularity of fermented foods has strongly increased based on their proven health benefits. One of these health-promoting products is water kefir, a fermented sugary beverage based on kefir grains (symbiotic colonies of yeast lactic acid and acetic acid bacteria). Based on previous knowledge and the uniqueness of each water kefir fermentation, the following project aimed to explore the microbial and chemical composition of a Colombian water kefir fermentation and its microbial consortium, through the integration of culture-dependent methods, compositional metagenomics and untargeted metabolomics. A strains culture collection of 90 strains was established, mainly consisting of individuals of Pichia membranifaciens, Acetobacter orientalis, Lentilactobacillus hilgardii, Lacticaseibacillus paracasei, Acetobacter pomorum, Lentilactobacillus buchneri, Pichia kudriavzevii, Acetobacter pasteurianus, Schleiferilactobacillus harbinensis, Kazachstania exigua, which can be further studied for their use in synthetic consortia formulation. In addition, metabarcoding of each fermentation time was done by 16S and ITS sequencing. The results show strong populations shifts of the microbial community during the fermentation time course, with an enrichment of microbial groups after 72h of fermentation., Metataxonomic results revealed Lactobacillus and Acetobacter as the dominant genera for lactic acid and acetic acid bacteria, whereas for yeast, Pichia membranifaciens was the dominant species. In addition, correlation and systematic analyses of microbial growth patterns and metabolites richness allowed the recognition of metabolic enrichment points between 72 and 96 hours, and correlation between microbial groups and metabolites abundance (e.g. Bile acids conjugates and Acetobacter tropicalis). Metabolomic analysis also evidenced the production of bioactive compounds in this fermented matrix, which have been associated with biological activities including antimicrobial and antioxidant. Interestingly, the chemical family of Isoschaftosides (C-glycosyl flavonoids) was also found, representing an important finding since this compound, with hepatoprotective and anti-inflammatory activity, hadn’t been previously reported in this matrix. We conclude that the integration of microbial biodiversity, cultured species and chemical data enables the identification of relevant microbial population patterns and the detection of specific points of enrichment during the fermentation process of a food matrix, that enable the future design of synthetic microbial consortia which can be used as targeted probiotics for digestive and metabolic health.